Significant Role of Islamic Work Ethic in Islamic Banking: A Systematic Literature Review and Direction for Future Research - Abdu Alifah; Anggraini Sukmawati (Universitas Darussalam Gontor, 2022)
Islamic Work Ethic (IWE) showed a significant role in various Islamic institutions, including Islamic banking. Unfortunately, only a few scholars studied the critical role of IWE in Islamic Banking and how it affected the whole organization. This study attempted to explore the degree of IWE implementation and its implications in Islamic banking. We investigated in-depth 22 articles related to IWE in Islamic banking between 2012-2021 through various reputable journal indexing sites. We concluded that the implication of IWE in Islamic banking is associated with work behavior/attitude, work outcomes, and organizational outcomes. IWE implications related to work behavior included organizational citizenship behavior (OCB), employee attitudes towards organizational change, and auditor's opinion and behavior. IWE implications related to work outcomes included employee job performance, organizational commitment, job satisfaction, and intrinsic motivation. IWE implications related to organizational outcomes included organizational performance, strategic performance measurement systems (SPMS), organizational culture, and customer satisfaction. Thus, due to the enormous implication of IWE in Islamic banking, it's supposed to be integrated with the HR management system, started from HR planning strategy, HR training & development program, performance appraisal system as well as benefit and compensation. Limitations and directions for future research are discussed further.